Nomenclature, diagnosis and management of drug-induced autoimmune-like hepatitis (DI-ALH): An expert opinion meeting report - Andrade-Bellido, Raúl Jesús; Aithal, Guruprasad P.; De Boer, Ynto S.; Liberal, Rodrigo; Gerbes, Alexander L; Regev, Arie; Terziroli Beretta-Piccoli, Benedetta; Schramm, Christoph; Kleiner, David E.; De Martin, Eleonora; Kullak-Ublick, Gerd A; Stirnimann, Guido; et al. (Elsevier, 2023)
Drug-induced liver injury (DILI) can mimic almost all other liver disorders. A phenotype increasingly ascribed to drugs is autoimmune-like hepatitis (ALH). This article summarises the major topics discussed at a joint International Conference held between the Drug-Induced Liver Injury consortium and the International Autoimmune Hepatitis Group. DI-ALH is a liver injury with laboratory and/or histological features that may be indistinguishable from those of autoimmune hepatitis (AIH). Previous studies have revealed that patients with DI-ALH and those with idiopathic AIH have very similar clinical, biochemical, immunological and histological features. Differentiating DI-ALH from AIH is important as patients with DI-ALH rarely require long-term immunosuppression and the condition often resolves spontaneously after withdrawal of the implicated drug, whereas patients with AIH mostly require long-term immunosuppression. Therefore, revision of the diagnosis on long-term follow-up may be necessary in some cases. More than 40 different drugs including nitrofurantoin, methyldopa, hydralazine, minocycline, infliximab, herbal and dietary supplements (such as Khat and Tinospora cordifolia) have been implicated in DI-ALH. Understanding of DI-ALH is limited by the lack of specific markers of the disease that could allow for a precise diagnosis, while there is similarly no single feature which is diagnostic of AIH. We propose a management algorithm for patients with liver injury and an autoimmune phenotype. There is an urgent need to prospectively evaluate patients with DI-ALH systematically to enable definitive characterisation of this condition.
Keywords: Hígado - Enfermedades; Hígado - Efectos de los medicamentos; Liver injury; Hepatotoxicity; Drug-induced liver injury; DILI; Autoimmune hepatitis; AIH; DI-ALH; Drug-induced autoimmune-like hepatitis; Epidemiology; Diagnosis; Management; Outcome